Suffering in the Epic of Gilgamesh Epic - Villiers, Gerda de (Old Testament essays, 2020)
This article examines moments of suffering in the Epic of Gilgamesh. Initially Gilgamesh himself causes much suffering by abusing his power as king and tormenting his subjects day and night. Enkidu is created to curb the king’s energy and to alleviate the distress of the people. Gilgamesh’s greatest joy in finding a true friend also turns into his greatest sorrow when Enkidu becomes ill and dies. Gilgamesh is inconsolable and his suffering drives him away from his palace and his city, in search of life everlasting. When a snake snatches away his last hope of living forever, he realises that life eternal is to be found in life here and now. The article concludes with some suggestions of appropriating Elizabeth Kubler Ross’ five stages of grief to the Epic of Gilgamesh.